Two new species of Tanaidacea (Crustacea, Peracarida) from Taiwan - Tzeng, You-Wei; Hsueh, Pan-Wen (Zootaxa, 2014)
Two new species, representing the genus Aparatanais of the family Paratanaidae and the genus Tanais of the family Tanaidae (both families belonging to the suborder Tanaidomorpha), are described in the present study. The genus Aparatanais, the family Paratanaidae and the superfamily Paratanaoidea are recorded for the first time from Taiwan. Aparatanais lenoprimorum sp. nov. departs from its congeners by the lack of subdistal teeth on the superior margin of the right mandible and without serration on left mandible lacinia mobilis. Tanais nuwalianensis sp. nov. is distinguished from its most similar congener, Tanais tinhauae, by the presence of a much smaller right mandible lacinia mobilis, fewer carpal spines on pereopods 2–6, fewer leaf-like setae on the distal margin of the propodus of Pereopod 6, and fewer inner setae on the pleopod basis. Morphological comparisons between members of the genus Aparatanais, as well as the genus Tanais are tabulated.